Leucism in Reithrodontomys mexicanus soederstroemi (Rodentia: Cricetidae), Quito, Ecuador - Ramírez-Jaramillo, Salomón; Bejarano-Muñoz, Patricia; Caiza, Angélica; Novillo, Marilyn; Moreno-Cárdenas, Pablo (Instituto de Ecología, A.C., 2019)
Leucism is a hypopigmentary decrease of skin or fur coat, which is presented throughout the body or as isolated whitish patches on different parts of the body "piebald"; without altering the pigmentation of the eyes, lips, blood vessels or harm to the immune system of the specimen. The specimen was identified in the Tababela plateau located in the inter-Andean valley of Pichincha, Ecuador, site of the new Quito airport. By using glue traps used to capture lizards, one individual of Reithrodontomys mexicanus soederstroemi showing leucism, was trapped in the wild. This individual presents an irregular distribution of melanin pigments throughout it’s body. This is the first case reported with leucism in nature for this endemic species of the inter-Andean xeric valleys near Quito.